Acquired Hemophilia A - Webert, Kathryn E. (Seminars in Thrombosis and Hemostasis, 2012)
Acquired hemophilia A is a rare, autoimmune disorder that is caused by autoantibodies that act as inhibitors to factor VIII. It is characterized by severe, unexpected bleeding that may be life-threatening. The incidence of acquired hemophilia A is ∼ 0.2 to 1.48 cases per 1 million individuals per year. Acquired hemophilia A has been associated with several clinical conditions including pregnancy, autoimmune or collagen vascular disorders, malignancies, drugs, respiratory disorders, and infections. However, in ∼ 50% of cases, no disease association is determined. Acquired hemophilia A should be suspected when a patient with no previous personal or family history of bleeding, presents with bleeding and an unexplained prolonged activated partial thromboplastin time (APTT) and other common causes of a prolonged APTT are ruled out. The treatment of acquired hemophilia A has two main goals: (1) to treat and/or prevent bleeding complications and (2) to eradicate the inhibitor. The recommended agents to be used for the treatment or prevention of bleeding in patients with acquired hemophilia A are the bypassing agents. Patients should be treated initially with corticosteroids, either alone or in combination with cyclophosphamide, to eradicate the inhibitor.
Keywords: acquired hemophilia A; inhibitors; bleeding